GESTURE PROGRESIF BANGUNAN SISTEM HUKUM INDONESIA - M Fauzi; Musthafa; La Syarifuddin (The Republic : Journal of Constitutional Law, 2025)
Legal challenges arise as society continues to evolve, necessitating rules to guide people's actions and serve as the basis for decision-making by law enforcement. Progressive law operates in the realm of ideas and advocacy to make law more beneficial to humanity thru a legal system that is liberating, conscientious, and utilizes spiritual intelligence in serving law to humanity. This goal seems inconsistent with legal positivism, which is the general pattern for the structure of written legal systems in modern countries. The study results indicate that some joints of the Indonesian legal system have gestures that can be used to progressively move the existing legal system. Based on Article 1 paragraph (3) of the 1945 Indonesian Constitution, Indonesia is a state of law with a tendency toward the rule of law that prioritizes justice over legal certainty based on written law. The gap between societal norms and dynamics can be filled either thru responsive legislation or thru the progressive legal discovery by judges. Judges are obliged to explore, follow, and understand the legal values and sense of justice that exist within society. The development of judicial review of legislative products in the Constitutional Court and the Supreme Court also shows a shift in perspective from merely textual thinking toward a more progressive legal way of thinking. The task of enforcing and upholding the law is one that requires seriousness and steadfastness against temptation, so what is needed is a good societal culture and law enforcement resources in order for the legal system to improve.